Assessment of Iron, Lead, Zinc, Cadmium and Chromium in Green Vegetables Irrigated with Domestic Waste Water. Issue 4 (3rd July 2016) - Ajaz, Humayun; Shiekh, A.J.; Umar, M.; Rabbani, F.; Mubeen, H.; Asif, Z.; Shah, Faheem
Abstract: In the present study, different vegetables irrigated with domestic waste water have been assessed for iron (Fe), lead (Pb), zinc (Zn), cadmium (Cd) and chromium (Cr). Transfer and daily intake of these metals to local population through food chain was also estimated. Health hazards due to their daily intake were also evaluated accordingly. The wastewater, its contaminated soil and irrigated vegetables were selected for this study. The samples of four vegetables namely turnip ( Brassica rapa ), Cabbage ( Brassica oleracea ), Coriander ( Coriandum sativum ) and Goosefoot ( Chenopodium album ) were acid digested and analyzed for heavy metals. The results showed that Fe is present in highest concentration followed by that of Pb, Zn, Cd and then Cr. In comparison, the cabbage contains highest concentration of metals whereas turnip least. The bioaccumulation factor and transfer of metals via vegetables in consumers (both adult and child) are also studied on the priority basis.